If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -2) = 16q Combine like terms: 3 + -2 = 1 4(1) = 16q Multiply 4 * 1 4 = 16q Solving 4 = 16q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-16q' to each side of the equation. 4 + -16q = 16q + -16q Combine like terms: 16q + -16q = 0 4 + -16q = 0 Add '-4' to each side of the equation. 4 + -4 + -16q = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -16q = 0 + -4 -16q = 0 + -4 Combine like terms: 0 + -4 = -4 -16q = -4 Divide each side by '-16'. q = 0.25 Simplifying q = 0.25
| c+c*7+2=12 | | 4(3n-7)+3=-3(-2n+8) | | 5b+9=7+2b | | -0.7w=5.6 | | 5x+27=2x+12 | | -11+9-2x-11-1=-13 | | 8t=400 | | (a+8)(a+2)=0 | | (x^2-x-1)(x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x | | 7+4(3v-4)=-3(3v-3)+7v | | 4x-15=2x+9 | | x^7+2x^6-5x^5-13x^4-13x^3-5x^2+2x+1=0 | | 9w^2-75w-54= | | 5y-3=4(y+3) | | (8x+9)(2x+4)=0 | | 5n+3+9= | | 3d^2-13d+12= | | r+(-2)=-8 | | 3=8-x | | -3b+7=8b-3 | | x^2=52-9x | | 7u+3-2(-2u-3)=2(u-3) | | z^4=-16i | | -4x+2=-7x+11 | | 3x(5x+36)=180 | | -16s-126+4(4s+32)=0 | | 8.1=x-12.5 | | 4x-8=x-5+3x | | 4x+2(-2x+7)=16 | | 16t^2+35t+5=0 |